Two letters of commendation to st. Evfrosin of Pskov about the lands for the monastery (1450s — 1465) - Arsenii Postnikov (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2023)
The article reports on the discovery of new texts of Pskov charateic charters of the XV – beginning of the XVI century, originating from the patrimonial archive of the Three-Holy Eleazar Monastery. They were preserved in the form of lists around 1732. The discovery was made by the author during the work on the identification and scientific description of the available composition of documents of the XVI–XVIII centuries. in the collection of the Ancient Repository of the Pskov Museum. The study showed that the Copy Notebook found as part of the book binding includes lists with 21 letters. Among them are complete documents and their fragments. This publication presents the experience of studying two acts from the Copy Book of the Three-Holy Monastery. These are certificates No. 6 and No. 11 in order in the collection. They are remarkable in that they are directly related to the history of the monastery's creation, since in the middle of the XV century they were given to the Most Reverend Euphrosyne on the land for the monastery he had built. The plots of land were located in the Krivovitsky rural district of the Belsky ambush of Pskov County between the Tolva River and a small forest lake. Transferred from the previous owners "to oderen", that is, to full unconditional ownership, they created the core of the patrimony and remained with the current monastery, despite the later secularization of 1764. The same lands are part of the modern borders of the restored monastery. Temples, monastic cells, a cemetery, a refectory, a cow village, a hotel and all other buildings necessary for a statutory life are located on them. The new letters of the era of the Veche Pskov are a valuable source for the study of the ancient Pskov script, the ancient topography of the Pskov land, church history and monastic land ownership.